Introduction to Healthcare and Medical Robotics and Simulation a proposed General Education course - Guiao, Gabriel Ian G.
Introduction to Healthcare and Medical Robotics and Simulation is a proposed general education course to be taken by undergraduate health and allied sciences students of De La Salle Medical and Health Sciences Institute. This course aims to equip learners with fundamental knowledge and understanding of functions and purpose of healthcare and medical robotics and simulation in their future workplace. As a general education course to be taken in three (3) credit units (2.5 units/hours lecture, 0.5 units/hours laboratory), it is targeted to all undergraduate programs of the institute to be taken in their first year or second year of study. The proposed general education course shall have lecture and laboratory components similar to GE-PHY101 (Physics for Allied Health Professionals) and GE-CHM101 (Chemistry for Allied Health Professionals) wherein students will be able to gain theoretical and applied knowledge and skills pertinent to robotics and simulation.